Rural occupational transitions: transportation, identity, and new geographies - Ray, Dusty (Kansas State University, 2017)
Commercial trucking by its nature is a transient occupation, and those involved with commercial trucking can find themselves on the road and away from their homes for extended periods of time. Given the occupation’s transitory nature, why have some commercial drivers chosen to call rural America home when any place near a highway should suffice? Through the use of semi-structured interviews, this thesis attempts to explore whether rural truck drivers have any historical or geographical ties to the rural areas that they have chosen to live in. Using qualitative interview approach this thesis endeavored to find whether there are connections to the loss of agricultural or rural manufacturing jobs in a rural driver’s community and their decision to enter the occupation of trucking. In this way this thesis has attempted to discern to what extent structural changes in the rural economy over the last 40 years, may have played a role in a person’s decision to enter the occupation of trucking. This thesis has also attempted to elicit a phenomenological understanding of how they rural truck drivers understand themselves in relation to the larger American society through the work they perform.
Keywords: Commercial trucking; Rurality; Phenomenology; Sense of place; Occupation; Structural conflict